Tinjauan Yuridis Penggunaan Klausul Proteksi Diri Terhadap Akta Pernyataan Keputusan Rapat Perseroan Terbatas - Muhammad Ulinnuha (Universitas Islam Indonesia, 2020)
The purpose of this study is to determine the actions that should be taken by a Notary in making a Resolution Deed of a Limited Liability Company and the use of a self-protection clause in making the Resolution Deed of a Limited Liability Company which may serve as a protective shield for a Notary. This study uses a normative juridical research method. The results conclude that in making the Resolution Deed of the General Meeting of Shareholders, the Notary must be able to thoroughly, carefully and properly carry out his duties and positions; practicing the principle of prudence, as the Resolution Deed of the General Meeting of Shareholders is an akten partij, which means the Notary needs only to record what the parties desire in the Deed without changing, subtracting and adding the contents of the Deed. The existence of a self-protection clause in a Resolution Deed of the General Meeting of Shareholders cannot automatically become a protector for the Notary when a problem occurs in the future, as regulated in Article 65 of Law No. 30 of 2004 on Notary Positions (UUJN) and its amendments. that the Notary must be responsible for every deed they make